2020
DOI: 10.1111/trf.15805
|View full text |Cite
|
Sign up to set email alerts
|

rIL‐35 prevents murine transfusion‐related acute lung injury by inhibiting the activation of endothelial cells

Abstract: BACKGROUNDTransfusion‐related acute lung injury (TRALI) is an important cause of death associated with transfusion, and no specific clinical treatments are available. Endothelial cells are believed to play an important role in the development of TRALI. This study investigated whether IL‐35, an endothelial stabilizing cytokine could regulate the severity of antibody‐mediated TRALI in vivo.STUDY DESIGN AND METHODSHuman microvascular endothelial cells (HMVECs) were cultured in vitro, rIL‐35(2 μg/mL) was added bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…MPO activity was measured to assess inflammation in the lung. Consistent with previous studies ( 24 , 25 ), pulmonary neutrophil infiltration, as evidenced by increased MPO activity, was typically observed in TRALI mice ( Fig. 2A ).…”
Section: Resultssupporting
confidence: 92%
“…MPO activity was measured to assess inflammation in the lung. Consistent with previous studies ( 24 , 25 ), pulmonary neutrophil infiltration, as evidenced by increased MPO activity, was typically observed in TRALI mice ( Fig. 2A ).…”
Section: Resultssupporting
confidence: 92%
“…Therefore, other than IL-10 and IL-8, other cytokines may be also potential research targets for TRALI prevention and treatment. For example, Qiao et al (2020) preliminarily confirmed that IL-35 could prevent murine TRALI by inhibiting the activation of endothelial cells. The study of additional immunological factors in combination with previous research findings could shape the field of TRALI research.…”
Section: Other Factorsmentioning
confidence: 87%
“…IL-35, which belongs to the IL-12 cytokine family, is regarded as a novel immune-suppressive cytokine (149). IL-35 may alleviate disease states by inhibiting pulmonary endothelial proliferation, apoptosis, and activation (133,150). IL-35 treatment has been proven to prevent murine TRALI via inhibition of endothelial activation (133), which could provide new insights into therapeutic targets.…”
Section: Targeting Endothelial Activationmentioning
confidence: 99%